Cláusula geral da boa-fé objetiva como fundamento de concretização do sistema jurídico aberto - Soares, Daniela Oliveira (2020)
Objective good faith endowed the Civil Code system with flexibility, openness, and the possibility of adapting to constant social changes. In this sense, the General Clause of objective good faith is the foundation for the realization of the current open and mobile legal system. The new system has the possibility of accepting, the so-called limit cases, those that the law was not able to predict, and to judge them fairly, in the material sense of justice. In Brazilian Civil Law, objective good faith was confirmed through article 4, III, of the Consumer Protection Code, and later through the interpretation rule contained in article 113, in the General Clause of article 422, as well as through the General Clause of Article 187, all of the Civil Code of 2002. Objective good faith, sometimes has the function of principle, sometimes a general clause, and that what discriminates the expression good faith, as a general principle or general clause, is the function it has in the system context. The introduction of objective good faith, in the Brazilian legal system, meant great evolution, since, in addition to providing the opening system to adapt to constant social changes, it started to meet the new social requirements, adapted the civil system, to the constitutional commandments the dignity of the human person, justice, equity, operability and solidarism. Good faith, in its objective conception, is a rule of behavior, according to which the parties must act as upright, loyal, honest, truthful human beings, without causing damage to the other party, nor frustrating the expectation created by the other party, without justification. The principle of private autonomy and the mandatory force of contracts are restricted due to the principle of objective good faith. The principle of objective good faith has a threefold function, essential to the good performance of the order, allowing its adaptation to new social realities, in addition to adapting legal relations to the values of human dignity and material justice. The problem that involves the general clause of objective good faith, revolves around the power-duty attributed to the interpreter-applicator, which may incorporate a negative aspect if used with discretion, subjectivism and with the purpose of serving political and economic interests, creating injustices, uncertainty and legal uncertainty